(3GdeSDhdjI GdLfGFjI ddbGOI h GdQDSGA h GdOaY HChGeQge CeGe GdbVGA GdLfGFj GdOhdj (B/ s - (3ShjOj, Sja ZGfe(B.s ((3OHj (B: s (3eQcR GdHMhK h GdOQGSGJ HCcGOjejI TQWI OHj,s, 2013)
(3jQcR GdHMK Ydi JMOjO eVehf eHOC eSFhdjI GdbGOI, hPdc ef CLd GdJMbb ef eOi GSJbQGQ GdeHOC hGdGYJQGa Hg ef bHd GdeLJeY GdOhdj GdeYGUQ, hef Ke JhVjM GdCSGS GdbGfhfj GdPj jecf Cf JSJfO Ydjg GdeMGce GdLfGFjI GdOhdjI YfO ESfGO GdeSDhdjI GdLfGFjI Ydi CTNGU WHjYjjf habkG deHOC eSDhdjI GdbGOI(B. (3hjSJYQV GdHMK GdYfGUQ GdbGfhfjI GddGRe JhGaQgG dbjGe eSDhdjI GdbGOI, hjhVM ajeG EPG cGf GdefUH GdbjGOj jTcd SHHkG ef CSHGH JTOjO GdYbhHI Ce dG(B. (3hjHjf ajeG EPG cGfJ ChGeQ GdQDSGA JYJHQ SHHkG ef CSHGH JNaja GdYbhHI Ydi GdeQDhSjf GdPjf bGehG HGQJcGH GdLQGFe GdEfSGfjI JfajPkG dChGeQ QDSGFge, hjfGbT eG EPG cGf ef GdLGFR ddeQDhSjf GdOaY HChGeQ GdQDSGA dfaj GdeSDhdjI GdLfGFjI Yfge(B.s
Keywords: (3eSDhdjI GdbjGOI (B((3GdbGfhf GdOhdj(B)s; (3GdQDSGA h GdeOjQhf s -- (3bhGfjf h JTQjYGJ(B.s; (3GdeSFhdjI GdLfGFjI (B((3bGfhf Ohdj(B)s; (3GdbGfhf GdOhdj GdLfGFj(B.s